Wewenang KPK Dalam Penanganan Tindak Pidana Korupsi yang Dilakukan Oleh TNI Aktif Dikaji Dari Teori Hukum Pembangunan - Telaumbanua, Yoses Ondrasi; Pangajang, Hasrudin; Busmtami, Simona (Sahabat Publikasi, 2023)
This study examines the authority of the KPK to perform duties and functions in terms of investigation, investigation and prosecution of corruption crimes carried out by active TNI. This research uses a normative type of research and uses a Statute Approach that examines related laws and regulations in this study, and uses a Conceptual Approach that examines legal principles or related legal principles in this study. Based on the results of research conducted by the author, it is concluded that the Corruption Eradication Commission (